Civil-military relations in post-Deng China from symbiosis to quasi-institutionalization - Li, Nan 1956- (Springer, 2021)
1. Introduction: Analytical Puzzle, Literature Review, Central Arguments, And Methodological Considerations -- 2. Evolving Functions Of The Party And Political Work System In The PLA -- 3. The PLA And Intra-CCP Leadership Power Struggle In The Eras Of Mao Zedong And Deng Xiaoping -- 4. Top Leaders And The PLA In The Post-Deng Era -- 5. Circulation Of Elites Across The Civil-Miliary Institutional Boundareis -- 6. Explaining The Evolution Of Civil-Military Relations From Symbiosis To Quasi-Institutionalization In China -- 7. Major Implications For China’s National Security, Political-Military Cooperation, And Inter-Agency Policy Coordination -- 8. Conclusion: Institutional Changes And Possible Role Of The Miltiary In Transition To The Post-Xi Jinping Leadership.
Keywords: Zhong guo gong chan dang; Geschichte 1989-; Militär